2022
DOI: 10.1001/jamapediatrics.2022.3424
|View full text |Cite
|
Sign up to set email alerts
|

Top Surgery and Chest Dysphoria Among Transmasculine and Nonbinary Adolescents and Young Adults

Abstract: ImportanceTransgender and nonbinary (TGNB) adolescents and young adults (AYA) designated female at birth (DFAB) experience chest dysphoria, which is associated with depression and anxiety. Top surgery may be performed to treat chest dysphoria.ObjectiveTo determine whether top surgery improves chest dysphoria, gender congruence, and body image in TGNB DFAB AYA.Design, Setting, and ParticipantsThis is a nonrandomized prospective cohort study of patients who underwent top surgery between December 2019 and April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…Research specifically regarding chest masculinsation mastectomy for minors and young adults, is of poor quality and makes surprisingly confident statements of benefit. For example, Ascha et al (72), considered the psychological impact of chest masculinisation mastectomy on 14-24 year olds but had only a three month follow up and 14% drop out. They argued that there is no evidence to support delaying chest masculinisation mastectomy based on age and claimed that their findings would, "help dispel misconceptions that gender-affirming treatment is experimental."…”
Section: Discussionmentioning
confidence: 99%
“…Research specifically regarding chest masculinsation mastectomy for minors and young adults, is of poor quality and makes surprisingly confident statements of benefit. For example, Ascha et al (72), considered the psychological impact of chest masculinisation mastectomy on 14-24 year olds but had only a three month follow up and 14% drop out. They argued that there is no evidence to support delaying chest masculinisation mastectomy based on age and claimed that their findings would, "help dispel misconceptions that gender-affirming treatment is experimental."…”
Section: Discussionmentioning
confidence: 99%
“… 45 A recent multicenter, prospective, control-matched study showed that gender-affirming chest masculinization surgery was associated with significant improvement in chest dysphoria, gender congruence, and body image satisfaction 3-months post-surgery and that surgery was associated with low complication rates. 46 …”
Section: Gender Affirmative Carementioning
confidence: 99%
“…In the setting of dire health disparities and inconsistent access to care both geographically and through insurance coverage, additional research demonstrating the benefit of genderaffirming surgery in this population is needed. This article by Ascha et al 13 is the first to look at patient-reported outcomes in adolescent and young adult (AYA) patients after top surgery. It is a multicenter, prospective, matched study looking at AYA TNG patients who pursue top surgery vs those who do not.…”
Section: Gast MD Msmentioning
confidence: 99%